2006
DOI: 10.21236/ada459448
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated Spacecraft Architectures Seeding Study

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…where nontraditional attributes of maintainability, scalability, flexibility, and responsiveness were included in addition to mass and cost [11]. To explore the trade space of fractionated spacecraft the software named GT-FAST was developed not only to enumerate all possible architectures but also to analyze and quantify the cost and benefit of each architecture [12,13].…”
Section: Chu Guo and Gillmentioning
confidence: 99%
“…where nontraditional attributes of maintainability, scalability, flexibility, and responsiveness were included in addition to mass and cost [11]. To explore the trade space of fractionated spacecraft the software named GT-FAST was developed not only to enumerate all possible architectures but also to analyze and quantify the cost and benefit of each architecture [12,13].…”
Section: Chu Guo and Gillmentioning
confidence: 99%
“…However, maintainability, scalability, flexibility, and responsiveness all improve with fractionation, and they conclude that if these attributes are valued enough, then the advantage quickly shifts to fractionated spacecraft. 20 Next, Brown and Eremenko apply a value-centric approach to the fractionation of space architectures in their discussion of DARPA's F6 program. From their experiences in this program, the authors found that disaggregated architectures offer greater flexibility, robustness, and scalabilty over more traditional monolithic space vehicles, and if stakeholders are sufficiently convinced of the value of such attributes in a space architecture then they will accept the costs and risks associated with switching to the fractionated paradigm.…”
Section: F Aggregation or Disaggregation Of Orbital Assetsmentioning
confidence: 99%
“…More recently, the need for more capacity in strategic orbital and the necessity to best utilize the available spectrum, has revived efforts to place more than one satellite at the same orbital slot (co-location). The concept of fractionated spacecraft that co-working modules linked by ISL returns to the center of interest [1]- [5]. The F6 program is so challenged and aggressive that the progress had been delayed several times and no significant development has been reported.…”
Section: Introductionmentioning
confidence: 99%